Harnessing phage display technology for generating fully human IgG antibodies that neutralise elapid neurotoxins - Karatt Vellatt, Aneesh (2019)
Snakebite constitutes a major health concern in rural, tropical parts of the world, causing mortality, morbidity and suffering to millions of victims. Members of the notorious elapid snake family are known for their potent neurotoxic venom, the clinical manifestation of which is descending paralysis in envenomed victims. The venoms of the two most feared species in their respective geographical regions of sub-Saharan Africa and Southeast Asia, Dendroaspis polylepis and Naja kaouthia, were analysed by toxicovenomics and their medically most important toxins were identified. A diverse panel of single-chain variable fragment (scFv) binders were isolated against two of the most important toxins from these snakes (dendrotoxin 1 and α-cobratoxin) from the IONTAS human naïve antibody library using phage display technology. The most promising binders were converted to human IgG1 format, transiently expressed in HEK293 cells, and tested in vivo in CD-1 mice. Several IgGs showed full protection (>24 hours) at low doses against both toxins and are being further investigated for their ability to cross-neutralize homologous snake venom toxins. These results break new ground as the first report of fully human IgGs capable of neutralizing animal toxins.